Overlapping organizations, political crises, and coexistence: complementarity and fragmentation in south american and african regionalisms - Ribeiro, Clarissa Correa Neto (2020)
The present research has the occurrence of overlapping regionalisms as its object, with a comparative cut for South America and Africa. The purpose of this thesis is to study types of institutional interaction and to analyze the effects of overlapping in the coexistence between regional processes in order to understand their dynamics in the above-mentioned regions. The observation of organizational behaviors and interaction is made through cases of political crises on the selected regions, as we assume that the interactions between overlapping regional organizations in those situations would tend to be more fragmenting than complementary as they go beyond the traditional membership-mandate relationship. Therefore, we also analyze overlapping performances and seek to understand how regional organizations will behave and interact while dealing with political crises, which constitute critical junctures, in accordance with the theoretical and methodological framework of the thesis. This work aims to produce a broad qualitative analysis of the given regions by considering applicable cases that cover all of the sub-regions and hence to contribute to the field of comparative regionalism by providing generalization and institutional learnings which are not derived by a given model of regionalism, but nonetheless based on a cross regional approach. The data is processed through document analysis and further systemized via the construction of presence and absence exercises, consisting on testing of hypotheses and dyadic relationships.